2010
DOI: 10.1007/s11244-010-9538-0
|View full text |Cite
|
Sign up to set email alerts
|

CuFe2O4 Nanoparticles: A Magnetically Recoverable Catalyst for Selective Deacetylation of Carbohydrate Derivatives

Abstract: An efficient protocol for the rapid room temperature deacetylation of carbohydrate derivatives using CuFe 2 O 4 nanoparticles as an inexpensive and reusable catalyst is presented. After separation of the catalyst with an external magnet, the reaction products are easily obtained in good purity and excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…These significant peaks appeared both in fresh and reused catalyst (Supplementary Figure S1). In addition, the powder Xray diffraction analysis, [59] showed identical peaks for both the fresh and recovered CuFe2O4 nanoparticles (Supplementary Figure S2).…”
Section: Methodsmentioning
confidence: 87%
“…These significant peaks appeared both in fresh and reused catalyst (Supplementary Figure S1). In addition, the powder Xray diffraction analysis, [59] showed identical peaks for both the fresh and recovered CuFe2O4 nanoparticles (Supplementary Figure S2).…”
Section: Methodsmentioning
confidence: 87%
“…Scanning electron microscope (SEM) studies of both fresh and used catalysts were carried out to understand the morphology of the catalyst. Figure S1 showed the SEM, [26] images of the fresh and the used catalyst after the fourth cycle, respectively. Interestingly, it is showed that there was no distinguished alteration in the morphology of the catalyst before and after the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of the CuFe 2 O 4 nanoparticles showed that identical peaks appeared in the fresh catalyst and the used catalyst. FTIR [28] spectra are presented in Figure S3a,b (Supporting Information), and significant bands in the range 600-400 cm -1 prove the presence of CuFe 2 O 4 peaks. These peaks appeared both in the fresh and reused catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[27] As a part of our ongoing research program and continuous interest in the field of cross-coupling reactions aimed at the exploration of new synthetic protocols focused on the development of reusable catalysts for the formation of aryl-selenium bonds, Cu/Febased catalysts were examined for their catalytic efficiency, due to their economic and industrial importance. We herein report a significant finding on the use of magnetically separable copper ferrite (CuFe 2 O 4 ) nanoparticles [28] as catalysts for C-Se coupling processes. To the best of our knowledge, this is the first report on the copper ferrite (CuFe 2 O 4 ) nanoparticle catalyzed coupling of aryl iodides/bromides with diphenyl diselenide to form aryl selenides in a very efficient manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation